Pemberdayaan Ibu-Ibu PKK Melalui Pemanfaatan Minyak Jelantah Menjadi Lilin Aromaterapi di Lingkungan Desa Duwet Kecamatan Baki Kabupaten Sukoharjo - Wijayanto, Danar Susilo; Azmi, Maimunah; Isnanto, Irham Hasri; Damayanti, Rahma; Rahmawati, Karisma; Pertiwi, Anisa Ayu; Rahmadzani, Defani Rizky; Efendi, Mohamad Syarifudin; Alfian, Muhammad; Anggreni, Mahera; Yusnawati, Septian (Society : Jurnal Pengabdian Masyarakat, 2023)
Used cooking oil is a liquid household waste that is not permitted to be discharged into waterways. Used cooking oil discharged directly into waterways causes scale on pipes, poisons animals that live in the water, and potentially harms the environment because oil cannot be broken down by water. Therefore, recycling of used cooking oil is a common obligation to reduce environmental damage due to water pollution. In order to reduce the potential environmental damage caused by used cooking oil, the FKIP 127 KKN Group of Universitas Sebelas Maret held a community empowerment activity by implementing activities in order to utilize used cooking oil into aromatherapy candles for PKK women in Duwet Village. The method used in this community empowerment activity is interactive lectures accompanied by experiments. The results of this activity are 1) participants in the socialization activity are able to understand the dangers arising from the disposal of used cooking oil in waterways and 2) participants in the socialization activity understand the process of recycling used cooking oil into aromatherapy candles. The conclusion is that the effort to tackle water pollution due to used cooking oil by recycling it into aromatherapy candles has the support of the community empowerment participants who are members of the PKK organization.